The pre-nesting behaviour and time budget of the Harlequin Duck Histrionicus histrionicus - Inglis, I R; Lazarus, John; Torrance, R (Wildfowl, 1989)
We describe the behaviour patterns, time budgets, diurnal rhythms and spacing patterns of the Harlequin Duck in the pre-nesting period. The study area was on the Lax, a river in northeast Iceland, where the population is at a high density, containing pairs and unpaired males in the ratio 2:1. Birds spent much of their time resting on islands close to the water and dived for food in the fast stretches of the river. Females sat and preened more than males. They also had longer dive times. Agonistic and pre- and post-copulation displays are described. Males were not territorial but guarded their mates vigorously. Females incited their mates and joined them in agonistic encounters. Extra-pair copulation by paired males was not observed and unpaired males spent little time attempting to copulate with females. These mating strategies are discussed in the context of anatid strategies generally. The displays and time budget data are related to those of other ducks that inhabit fast-flowing rivers.